KOORDINASI KEPOLISIAN DENGAN DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DALAM MENANGANI KASUS KEKERASAN SEKSUAL KABUPATEN ENREKANG - Youvita, Youvita; Sudarmi, Sudarmi; Mone, Ansyari (Universitas Muhammadiyah Makassar, 2023)
This study purposed to find out the Coordination of the Police with the Office of Women's Empowerment and Child Protection in Handling Cases of Sexual Violence in Enrekang Regency. This study used qualitative methods and consisted of 4 informants. The results of the study showed that the Coordination of the Police and the Office of Women's Empowerment and Child Protection in Handling cases of sexual violence were quite good and effective. From the perspective, namely (1). the efforts of the police agency and the women's empowerment office in handling cases of sexual violence in Enrekang Regency had made efforts in assisting sexual violence cases, (2) the unit of action in the coordination process between the women's empowerment service in handling cases of sexual violence in Enrekang Regency was still unconscious in every member of the agency, (3 ) common goals by providing direction to each member when there was a dispute at work so that the coordination process in dealing with cases of violence run effectively.